Fundamental and Technical Analysis of IPO Company Stocks in 2014 - Doly Silado Sijabat; Fifi Swandari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to identify and analyze the stocks of companies that went IPO in 2014 using fundamental and technical analysis with the variables Return on Assets (ROA), Return on Equity (ROE), Earnings per Share (EPS), Debt Equity Ratio (DER), Price Earning Ratio (PER), Price Book Value (PBV) and Trading Volume (VP). The approach used in this research is quantitative, with a purposive sampling data collection technique and a total sample size of 126. The data analysis technique used is panel data regression with a random effect model. The results showed that Return on Assets (ROA), Return on Equity (ROE), Debt Equity Ratio (DER), Price Earning Ratio (PER), Price Book Value (PBV), and Trading Volume (VP) had no effect, and were not significant on the IPO share price in 2014, while Earnings per Share (EPS) had a positive and significant influence on the IPO share price in 2014. The variables jointly affected the IPO share price in 2014.